2006
DOI: 10.2105/ajph.2004.047688
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity and Women’s Use of Complementary and Alternative Medicine in the United States: Results of a National Survey

Abstract: CAM use among racial/ethnic groups is complex and nuanced. Patterns of CAM use domains differ among groups, and multivariate models of CAM use indicate that ethnicity plays an independent role in the use of CAM modalities, the use of CAM practitioners, and the health problems for which CAM is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
87
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 16 publications
13
87
0
4
Order By: Relevance
“…1 Fifteen out of the 20 survey questions were modeled after existing questions that have been used in health care survey research. The initial 8 baseline demographic questions (#1-8) for this survey were developed to be almost identical to those generated by Kronenberg et al 6 The remaining 12 survey questions were predominantly adapted from the The 3-page survey was printed only on one side of the paper in an attempt to prevent participants from missing questions that might be printed on the back of any page. The survey was printed in Arial size 11 font.…”
Section: Instrument Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Fifteen out of the 20 survey questions were modeled after existing questions that have been used in health care survey research. The initial 8 baseline demographic questions (#1-8) for this survey were developed to be almost identical to those generated by Kronenberg et al 6 The remaining 12 survey questions were predominantly adapted from the The 3-page survey was printed only on one side of the paper in an attempt to prevent participants from missing questions that might be printed on the back of any page. The survey was printed in Arial size 11 font.…”
Section: Instrument Developmentmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] In one study, for example, Barnes et al 10 demonstrated that 43.1% of white adults sought out CAM treatments in comparison to 25.5% of blacks. Furthermore, there is minimal research that provides an explanation as to why blacks use CAM less often.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The demography of chiropractic patients is similar to that of the United States and crosses most social and economic categories, although minorities and lowest social and economic groups tend to seek out the care of a DC less frequently. 4 Previous assessments of chiropractic treatment tables in teaching clinics, although few in number, have found pathogenic microbes and allergens on table surfaces. [5][6][7][8][9] Hand hygiene and proper surface sanitizing are known to reduce the spread of pathogenic microbes in health care settings as well as reduce the presence of surface pathogens on treatment tables.…”
Section: Introductionmentioning
confidence: 99%
“…При этом основным методом коррек-ции и профилактики климактерических рас-стройств на сегодняшний день остается за-местительная гормональная терапия (ЗГТ), однако ее применение нередко связано с развитием различных осложнений и наличи-ем противопоказаний у некоторых женщин [11,12]. Публикации результатов исследований Heart and Estrogen/Progestin Replacement Study (HERS), Women`s Health Initiative (WHI), Million Women Study (MWS) в средствах массовой ин-формации стали причиной массового отказа от ЗГТ женщин по всему миру, что еще больше актуализировало интерес к альтернативным способам облегчения приливов жара [13,14]. Фитоэстрогены, психотропные препараты, средства, действующие на вегетативную нерв-ную систему, мультивитаминные комплексы, ра-стительные экстракты с большим или меньшим успехом используются в клинической практике.…”
unclassified